Correction of movement patterns of skaters through feedback on the distribution of plant pressure in speed running - Sushchenko V.P. ,; Vasyuk V.E. ,; Bykov D.Yu. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the possibilities of correcting movement patterns of speed skaters using feedback on the distribution of plantar pressure in speed running. Methods and structure of the study. The pilot experiment involved an athlete with many years of experience in international speed skating competitions. To record the distribution of plantar pressure during push-off in skating locomotion, the F-scan system (Tekscan, USA) was used. Based on the results of the first testing, the athlete focused on improving his technical readiness for six weeks. During repeated testing, changes were observed in the characteristics of the implementation of efforts during take-off in high-speed running on ice. Results and conclusions. The use of feedback techniques in the training process of qualified speed skaters based on plantar pressure distribution indicators helps to improve the individual model of take-off technique in high-speed running on ice, both in a straight line and along a turn.